Borage oil intake by overweight young adults: no effect on metabolic rate; beneficial effects on plasma triglyceride and HDL cholesterol readings. Issue 19 (16th August 2021) - DiSilvestro, Robert A.; Olivo Marston, Susan; Zimmerman, Autumn; Joseph, Elizabeth; Boeh McCarty, Carolynn
Abstract : Some research has raised the possibility that gamma linolenic acid (GLA) can increase resting metabolic rate (RMR), which can help with weight control. Abstract : Some research has raised the possibility that gamma linolenic acid (GLA) can increase resting metabolic rate (RMR), which can help with weight control. However, in overweight young adults with a family history of obesity, no effect on RMR was seen after a 6 weeks treatment with borage oil (880 mg GLA per day) or evening primrose oil (540 mg GLA per day). On the other hand, borage oil did lower plasma triglyceride readings and raise HDL cholesterol readings (mean starting values in normal range for triglycerides, borderline low for HDL). No effect was seen for body mass index, plasma total cholesterol, LDL cholesterol, or glucose. Thus, in the type of subjects studied here, borage oil, a source of GLA, did not show promise as a weight control aid, but could help prevent undesirable readings for two blood lipid measures.